Über-Reden durch An-Reden: Die phatische Funktion als Mittel zum Appell in englischen, spanischen und deutschen Werbetexten - Nord, Christiane (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Advertisements are intended to persuade the addressees to buy a particular product or service. In order to achieve this communicative purpose, text-producers make use of various strategies. Apart from directly appellative speech acts like recommendations, requests or invitations, they use referential, expressive, and phatic utterances as an indirect means of persuasion. The phatic function, which, according to Jakobson (1960), provides the appro-priate channel for communication, is of particular importance in this respect. If the channel does not work properly, the persuasive function will never reach its aim. In the following paper, a small corpus of English, Spanish and German advertising texts is analyzed in order to find the indicators of the phatic function which are instrumental in making persuasion work.